Protective effect of metformin against tuberculosis infections in diabetic patients: an observational study of south Indian tertiary healthcare facility - Srujitha Marupuru; Padmanav Senapati; Swathi Pathadka; Sonal Sekhar Miraj; Mazhuvancherry Kesavan Unnikrishnan; Mohan K. Manu (Brazilian Journal of Infectious Diseases, 2017)
Background: World Health Organization estimated that people with diabetes (DM) are at 2–3 times higher risk for tuberculosis (TB). Studies have shown that DM not only increases the risk of active TB, but also puts co-affected persons at increased risk of poor outcomes. Objectives: To determine the protective effect of metformin against TB in DM patients and also, to investigate the relationship between poor glycemic control and TB. Methods: A case–control study was conducted over 8 months, where cases and controls were selected based on the inclusion and exclusion criteria of the study. The diabetics diagnosed with TB were selected as study group (SG = 152) and without TB were as control group (CG = 299). Exposure status of metformin in both groups were analyzed. Results: The mean (SD) age of both CG and SG were 55.54 ± 11.82 and 52.80 ± 11.75, respectively. Majority of the subjects in the study were males. The mean hospital stay of SG and CG were 7 days and 6 days, respectively. Poor glycemic control (HbA1c > 8) observed in SG (51.7%) vs CG (31.4%). HbA1c value <7 is associated protective factor for TB occurrence [OR = 0.52 (95% CI 0.29–0.93)]. The protective effect of metformin against TB was 3.9-fold in diabetics (OR = 0.256, 0.16–0.40). Conclusion: Poor glycemic control among diabetics is a risk factor for TB occurrence. The result shows metformin use is a protective agent against TB infection in diabetics. Hence, incorporation of metformin into standard clinical care would offer a therapeutic option for the prevention of TB. Keywords: Diabetes, Metformin, Tuberculosis prevention